Pancreatic surgery: we need clear definitions - Mihaljevic, André Leopold; Saeedi, Mohammed al; Hackert, Thilo (Langenbeck's archives of surgery, 2019)
Background: Pancreatic surgery has undergone substantial changes during the last decades. Improved surgical techniques and perioperative care have contributed to improved outcomes and allow safe surgery with mortality rates below 5% in specialized centers today. In parallel, surgical indications and procedures have been continuously extended especially with regard to pancreatic cancer surgery including vascular resections and multivisceral approaches for advanced findings. Purpose: With the growing awareness of the need to report outcomes scientifically, it has become obvious that only standardized definitions allow a reasonable description and comparability with regard to indications, procedures, and especially complications. Consequently, a number of efforts have been undertaken to achieve this aim, including basic nomenclatures, preoperative definition of resectability, and specific outcome parameters.Conclusion: This review gives an overview on the development of international standardizations in pancreatic surgery and the current status and discusses their scientific importance and the most important current controversies in the context of the present literature as well as the ongoing future approaches in this field.
First online: 06 November 2018
Gesehen am 04.07.2019